PENGARUH MODIFIKASI PERMAINAN MEMANTULKAN BOLA TERHADAP KOORDINASI MATA-TANGAN ANAK TUNAGRAHITA SEDANG DI SLB PUTRA MANDIRI SURABAYA - , SANIA; ROHMAN KAFRAWI, FATKUR (Jurnal Kesehatan Olahraga, 2019)
Disabled children are having easy to switch attention that is difficult to concentrate on something and experiencing limitations in the move and has a less coordination of motion and has an IQ of IQ 55-40. Hand-eye coordination is important to improve the rough motor in the child disabled is in support of daily activities. This research aims to determine the effect of modification of the game reflecting the ball to the coordination of the hands of the child disabled is in the SLB Putra Mandiri Surabaya. This type of research is a pseudo-experimental study using the research design of One Group Pretest-Posttest Design. Sampling was conducted with Purposive sampling with a sample of 8 persons with moderate criteria of disabled, male gender, age 11-14 years, education level SMPLB and SMALB. The research instruments used in this study are hand ball throwing tests. Analytical techniques for obtaining data using test-t. Based on the results of the study that the 6-week training program was changed at the time of the pre-test of students who are in fact SLB Putra Mandiri Surabaya for 1.13 meter has increased to 1.88 meter at the time of post-test. Thus obtained a hand-eye coordination P value before and after the modification of the game reflects the ball of 0.00 < 0.05 and obtained Thitung of 4.583 > This 1.895 with a significant level of 0.05. It can be concluded that there are influences from the modification of the game reflecting the ball against the coordination of the hands of the child Tunagrahita. That this method needs to be practiced and socialized in schools of SLB that the modification of the game reflects the ball is very effective to improve the coordination of eyes and hands for children who are deaf. Keywords: Tunagrahita medium, hand-eye coordination, reflecting the ball.